Does early onset asthma increase childhood obesity risk? A pooled analysis of 16 European cohorts. Issue 3 (27th September 2018) - Contreras, Zuelma A.; Chen, Zhanghua; Roumeliotaki, Theano; Annesi-Maesano, Isabella; Baïz, Nour; von Berg, Andrea; Bergström, Anna; Crozier, Sarah; Duijts, Liesbeth; Ekström, Sandra; Eller, Esben; Fantini, Maria P.; et al.
The parallel epidemics of childhood asthma and obesity over the past few decades have spurred research into obesity as a risk factor for asthma. However, little is known regarding the role of asthma in obesity incidence. We examined whether early-onset asthma and related phenotypes are associated with the risk of developing obesity in childhood. This study includes 21 130 children born from 1990 to 2008 in Denmark, France, Germany, Greece, Italy, The Netherlands, Spain, Sweden and the UK. We followed non-obese children at 3–4 years of age for incident obesity up to 8 years of age. Physician-diagnosed asthma, wheezing and allergic rhinitis were assessed up to 3–4 years of age. Children with physician-diagnosed asthma had a higher risk for incident obesity than those without asthma (adjusted hazard ratio (aHR) 1.66, 95% CI 1.18–2.33). Children with active asthma (wheeze in the last 12 months and physician-diagnosed asthma) exhibited a higher risk for obesity (aHR 1.98, 95% CI 1.31–3.00) than those without wheeze and asthma. Persistent wheezing was associated with increased risk for incident obesity compared to never wheezers (aHR 1.51, 95% CI 1.08–2.09). Early-onset asthma and wheezing may contribute to an increased risk of developing obesity in later childhood. Children who have asthma or wheezing in early childhood may be at a higher risk of developing obesity http://ow.ly/HfKw30lhF3X